Samverkan för en hållbar landsbygdsutveckling - en studie av EU:s leadermetod - Magnusson, Andreas (SLU/School for Forest Management, 2012)
This study aims to illustrate the Leader approach and analyze the work of collaboration development within Leader. The idea has also been to describe some of the difficulties that might be encountered in this type of development work. By highlighting the strengths and weaknesses of this approach we hope to enhance the chance that future work in similar projects can be implemented more easily. Leader is a tool and methodology used in the European Union (EU) for work on sustainable rural development and it has been used since 1991. The purpose of Leader is that by supporting rural projects they will gain social capital and development in the rural communities. This development will be achieved through collaboration and local initiatives. Leader is currently used in Sweden's program for rural development that extends until 2013. In this study we developed a framework to make it possible to understand and evaluate collaboration. The framework also shows the steps needed to gradually achieve higher levels of interaction. Data were collected through qualitative interviews with people that are working with collaboration within Leader. The result from the study shows a need of an enhanced knowledge about the factors needed to develop partnerships. There are an awareness of the need for collaboration and the potential benefits that can be gained from collaboration. The study also shows that there only is one method of evaluation and that is a financial evaluation. At the time for the study there was no work to evaluate the gain of social capital from the approaches and methods in the Leader approach. Within the local work groups there are issues with inequality and members from different sectors of the society cannot participate at the same conditions. Leader is perceived as a good method to work with rural development at a local level with strategies designed for just that specific area. For Leader to be successful and properly implemented in the rural communities as a way to work on a common basis, the belief is that it requires an additional program period.